Does economic freedom boost growth for everyone? - Andreas Bergh; Christian Bjørnskov (Research Institute of Industrial Economics (IFN), 2019)
While the association between economic freedom and long-run economic growth is well documented, the parallel research literature on the distributional consequences of economic freedom is full of conflicting findings. In this paper, we take a step towards reconciling the two literatures by exploring the within-quintile growth consequences of changes in three different types of economic freedom: the size of government, institutional quality and policy quality. While the associations are theoretically ambiguous, we find evidence that economic freedom affects all parts of the income distribution equally, and some indications that the growth effects are largest for the poorest and richest quintiles.
Keywords: O40; O43; P16; 330; Economic freedom; Liberalization; Economic growth; Income inequality